CLINICAL PRESENTATION AND TREATMENT OF PHARYNGEAL TONSIL HYPERTROPHY IN CHILDREN WITH TORCH INFECTION - Nigora A. Rasulova, (Central Asian Journal of Medicine, 2025)
According to the data of the Tashkent Pediatric Medical Institute clinic, hypertrophy of the pharyngeal tonsils mainly develops in children aged 3 to 6 years 31 (51.6%) and from 7 to 10 years 17 (28.3%), while at the age of 11-16 years, there were 12 (20.1%) children. The main clinical symptoms indicating the presence of herpesvirus infection in OGM are regional cervical lymphadenitis (14.8%), as well as recurrent exudative otitis media (14.8%). The most effective treatment in children with GHM infected with herpesviruses is a combined method, including adenotomy with the prescription of antibacterial and antiviral drugs in the preoperative period (95%), while with surgical, conservative treatment, the effectiveness is lower (81.2 and 50%, respectively).